(3WGhhS aj CQV GdHWGQjbs (3McGjI Yf GdEHOGY hGdTLGYIs - (3LGdGgQ, Hj Ljgs; (3HdGfTGQO, cjfs; (3TejJ, hGQf EJTs; (3ecJHI LQjQs ((3GdQjGVs (3ecJHI LQjQs, 2024)
(3bUlI NjGdjlI ecJhHI HCSdhH YUQj Yf cjajI EXgGQ GdEHOGY hGdTLGYI aj eDSSGJ GdhbJ GdMGVQ(B. (3ojnbqOe gPG GdcJGH QDjkI LOjOkI dehVhY ege CdG hgh cjajI HK QhM GdJLOjO hGdEHOGY hGdJWhjQ aj HjFI GdYed ef NdGd ZQS CacGQ LOjOI HOdkG ef GdCSdhH GdJbdjOj GdPj YaG Ydjg GdRef(B. (3hfXkQG ddCSdhH GdQGFY hGdLPGH GdPj jfaQO Hg gPG GdcJGH, agh jCJj aj EWGQ bUI NjGdjI JJMOK Yf GdeDSSGJ hdcf HQhM GdYUQ GdMOjK(B. (3hGdbUI GdJj jShbgG EdjfG GdcJGH JJMOK Yf cjajI HfGA cjGf eDSSI JgJe HGdGHJcGQ hGdEHOGY hcjajI GdGSJaGOI ef ehGgH GdehXajf hWGbGJge hVeGf GdJRGege(B. (3gPG hJfaQO GdWHYI GdLOjOI ef gPG GdcJGH HfUGFM hCOhGJ hGSJQGJjLjGJ dTNUjGJ GdWGhhS, HGdEVGaI Edi LRA LOjO Yf cjajI JZjjQ KbGaI GdHWGQjb(B. (3hbO GSJWGY GdeDdaGf ef NdGd gPG GdcJGH Cf jQUOG MbjbI egeI Yf HjFI GdYed GdeYGUQI GdedjFI HGdeTcdGJ, hCKHJG HLOGQI Cfg aj GdEecGf EMOGK JZjjQ gGFd Yf WQjb GdGSJaGOI ef GNJdGaGJ CSGdjH Yed GdehXajf aj GdTQcIs
Keywords: (3GdCOH GdEfLdjRjs; (3GdbUU GdEfLdjRjIs